2015
DOI: 10.1016/j.molcel.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal mTORC2/PHLPP1/Akt Regulate Chaperone-Mediated Autophagy

Abstract: SUMMARY Chaperone-mediated autophagy (CMA), a selective form of degradation of cytosolic proteins in lysosomes, contributes to maintenance of proteostasis and to the cellular adaptation to stress. CMA substrates are delivered by a cytosolic chaperone to the lysosomal surface, where upon unfolding, are internalized through a membrane translocation complex. The molecular components that participate in CMA substrate targeting and translocation are well characterized but those involved in CMA regulation remain mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
274
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(288 citation statements)
references
References 36 publications
12
274
2
Order By: Relevance
“…PFK‐2 has a canonical CMA motif (Dr Ann Maria Cuervo, written communication, May 2016; Figure 6A) that can potentially bind hsc70. It has been recently shown that CMA is regulated by lysosomal‐targeted Akt1 activity in a mammalian target of rapamycin complex (mTORC) 2– and PH domain leucine‐rich repeat protein phosphatase (PHLPP1)–dependent manner (Figure 6B) 27, 28. Specifically, mTORC2 phosphorylates and activates Akt1, thereby decreasing CMA.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…PFK‐2 has a canonical CMA motif (Dr Ann Maria Cuervo, written communication, May 2016; Figure 6A) that can potentially bind hsc70. It has been recently shown that CMA is regulated by lysosomal‐targeted Akt1 activity in a mammalian target of rapamycin complex (mTORC) 2– and PH domain leucine‐rich repeat protein phosphatase (PHLPP1)–dependent manner (Figure 6B) 27, 28. Specifically, mTORC2 phosphorylates and activates Akt1, thereby decreasing CMA.…”
Section: Resultsmentioning
confidence: 98%
“…A, A schematic of PFK‐2 indicating a putative CMA consensus sequence, catalytic cores, and known phosphorylation sites (starred). B, Lysosomal localized protein kinase B (Akt) 1 is phosphorylated and dephosphorylated by mammalian target of rapamycin complex (mTORC) 2 and PH domain leucine‐rich repeat protein phosphatase (PHLPP) 1, respectively 28. Phosphorylated Akt1 prevents CMA.…”
Section: Resultsmentioning
confidence: 99%
“…It is thus possible that different transcription factors co-exist to assure proteostasis under several circumstances and in distinct cell types. In fact, levels of basal CMA activity and the amplitude of the induction varies among different cell types [12,16,36,37]. Importantly, this novel NFE2L2-LAMP2A axis is conserved in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This step was repeated twice to wash the lysosomal-enriched fraction. Lysosomes active for CMA were isolated by centrifugation of the lysosomal-enriched fraction (light mitochondria and lysosomes) in a discontinuous metrizamide (AK Scientific, 69,696) density gradient [37,56]. The fraction of broken lysosomes at the moment of isolation was measured using the HEX/β-hexosaminidase latency assay [57].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation